Humanitarian Aid as an Instrument of Indonesia's Public Diplomacy in the Papua Issue: A Case Study of Vanuatu (2016–2023) - Firman Fauzi (International Journal Labs, 2026)
Indonesia's humanitarian assistance to Vanuatu has increased significantly since 2016, with a value of around US5.8 million in 2022. The assistance is realized through natural disaster response, the construction of health facilities, and capacity building programs, and is positioned as part of Indonesia's public diplomacy efforts to reduce international pressure related to the Papua issue. However, this increase in the intensity of humanitarian aid was not followed by a significant change in public perception or political attitudes in Vanuatu. Survey data shows that about 68 percent of Vanuatu people still support Papuan independence, while digital campaigns such as #FreeWestPapua with more than five million interactions continue to reinforce the pro-independence narrative in transnational public spaces. At the government level, Vanuatu has consistently raised the issue of Papua in various international forums, reflecting the gap between Indonesia's soft power efforts and the political results achieved. This study uses a single qualitative case study design with a time span of 2016–2023, through document analysis, tracing of humanitarian aid processes, media and social media content analysis, and limited observation. The theoretical framework of this research integrates Joseph Nye's concept of soft power and